An exploration of the opportunities and challenges of using digital technology to support social communication in non-verbal autistic students in three Saudi Arabian schools - Alassaf, Mohammed (2024)
The global rise in autistic children has raised concerns and emphasised the need to tackle its core issues, including social communication (SC) difficulties. The intent of this research was to explore how digital technology is being implemented to support SC in NV autistic students in light of teachers’ experiences and perspectives in mainstream inclusive schools in Saudi Arabia. The context for the research is Saudi Arabia, where digital technology integration for students with learning disabilities is increasing significantly under educational reforms aligning with Saudi Vision 2030. This issue clearly merits further investigation given the paucity of research relating to SC among NV autistic students in the Saudi context. In doing so, the study reported here further assessed the role and influence of digital technology in supporting pertinent SC precursors – in particular, joint attention, social orientation, engagement, and theory of mind – in NV autistic students keeping in view interaction between teacher’s guidance, digital technology and impact of context in three different school setting. The study was informed by Vygotsky’s social constructivist theory (Vygotsky, 1978) to explore how teachers applied digital technologies across the curriculum and interactive activities to provide opportunities for SC of NV autistic students in a mainstream inclusive school setting. The research design drew upon multiple qualitative case study research methodologies, exploring the opinion and perception of eleven teachers using semi-structured interviews and observations of nine NV autistic students from three schools in Saudi Arabia. The findings highlighted the teachers’ perspectives on the available opportunities and challenges as contextual factors that create or limit the conditions required to enable digital technology to support NV autistic students’ SC in the classroom, followed by determining further contributions these digital technologies may provide in teaching and learning processes. Thematic analysis of the case studies indicated that technology tools, along with the mediation of other instructional and behavioural techniques, certainly facilitate, supplement, and reinforce the SC and learning of NV autistic students. The findings indicated the efficacy of digital technologies along with the use of instructional approaches and strategies such as scaffolding and prompting, motivating and engaging these students in shared and collaborative activities, in engaging students with social engagement, orientation, and theory of mind (ToM). The study further demonstrated influencing factors in use of digital technologies including the provision of technological accommodations and resources (applications specific for SC, Arabic versions of applications, provision of devices for each student for individual practices, and better layout and facilities of resource rooms), the provision of assistance staff, and better teacher training and expertise. However, the contrasting views also indicated that the use and execution of digital technologies entail various challenges in the way teachers use them with autistic students, such as technical, support, and supervisory barriers., However, the extent to which the SC enabled by digital technologies may be applied to different situations remains questionable. The thesis concludes by identifying the factors affecting the appropriate integration of digital technologies for NV autistic students through the development of best practices in the use of such tools. The research suggests that future studies should focus on developing teachers’ technological competencies specific for enabling SC. Moreover, the attention of authorities is directed towards the facilitation of better standard assessment procedures to characterise and integrate provisions, specifically the technological accommodations, for NV autistic students.